Long-term follow-up of retinal sensitivity assessed by microperimetry in patients with internal limiting membrane peeling. Issue 1 (January 2022) - Blautain, Benjamin; Glacet-Bernard, Agnès; Blanco-Garavito, Rocio; Toutée, Adélaïde; Jung, Camille; Ortoli, Manon; Souied, Eric H
Purpose: To evaluate anatomical and functional changes in patients with vitreomacular interface disease after internal limiting membrane (ILM) peeling, using microperimetry along with usual clinical and multimodal retinal imaging. Methods: Patients with vitreomacular interface disease requiring vitrectomy underwent multimodal retinal evaluation, including visual acuity assessment, fundus color photograph, Spectral-Domain Optical Coherence Tomography, Optical Coherence Tomography-Angiography, and microperimetry. They were examined at baseline (M0), 6 months (M6) and 18 months (M18) after surgery. Retinal sensitivity was subdivided into three concentric polygons: Large, Medium, Small. Results: Eleven eyes of 11 patients were analyzed, including 10 epiretinal membranes (ERMs). Best-corrected visual acuity (BCVA) improved in all patients from 0.51 logarithm of the minimal angle of resolution (logMAR) to 0.067 ( p = 0.0074). Retinal sensitivity improved between M0 and M6 in all polygons and continued to improve between M6 and M18 for polygons Medium (M) and Small (S) with no statistical significance. At M18, BCVA and retinal sensitivity were similar in the operated eye compared with the fellow eye for all patients. Dissociated optic nerve fiber layer appearance was observed in 8 patients at M18. It was not correlated with either retinal sensitivity or BCVA or microscotomas. No recurrence of ERM or macular hole occurred during follow-up. Conclusion: After surgery, the retinal sensitivity assessed by microperimetry gradually improved until the 18th month and was not different from the values of the fellow eye. These results seemed to confirm that ILM peeling can be an effective and safe technique to treat patients with vitreomacular interface disease.